Effect Of Ethanolic Leaf Extract of Cocor Bebek (Bryophyllum Pinnatum) on The Attenuation Of Thermal Hyperalgesia - Wulandari, Diah Ayu; Harwoko, H.; Baroroh, Hanif Nasiatul (Journal of Nutraceuticals and Herbal Medicine, 2018)
Cocor bebek (Bryophyllum pinnatum) has been proven as analgesics for relief of acute pain. Flavonoid is one of the compounds in Bryophyllum pinnatum which is potentially developed as analgesics for the treatment of chronic inflammatory pain. This study was conducted to determine the effect of ethanolic leaf extract of Bryophyllum pinnatum as attenuation of thermal hyperalgesia in rats with chronic inflammatory pain. This study used a completely randomized design with complete Freundâs Adjuvant/CFAinduced chronic inflammatory pain in wistar rats, at the first day. Thirty rats were divided into 5 (five) groups (n = 6), consisting of a positive control (ketamine 10 mg/kg bw), negative control (CMC Na 0.5%), and three treatment groups of ethanolic leaf extract of Bryophyllum pinnatum with doses of 200, 400 and 600 mg/kg bw. The extract was given twice a week for four weeks,at day-3 and day-6. The effect of the treatment on the attenuation of thermal hyperalgesia was investigated by using hot-plate at day-7, day-14, day-21 and day-28 to measure latency and subsequently, the percentage of the increase in latency was calculated. Analysis of Variance (ANOVA) was employed to analyze the data and continued by Least Significance Different test (LSD). The ethanolic leaf extracts of Bryophyllum pinnatum at the doses of 200, 400, and 600 mg/kg bwhad effect of the attenuation of thermal hyperalgesia by increasing latency by 3.18, 4.33 and 6.12 seconds, respectively. The optimum dosage as antihiperalgesia was 600 mg/kg bw, with latency was increased to twice than those of negative control group.